2004
DOI: 10.3200/jach.52.5.197-202
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use Among Community College Students: Implications in Designing Healthcare Interventions

Abstract: The Internet has become a commonly used venue for seeking healthcare information. Young adults search the Internet for health information more than any other group, yet little is known about use patterns among community college students. The authors surveyed a diverse community college to assess students' use of the Internet for health-related information. More than 80% had home Internet access, regardless of race or gender. Men and women searched for health information in almost equal numbers. Most students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 3 publications
0
64
1
Order By: Relevance
“…30,31 Seventy-fi ve percent to 80% of adolescents and young adults have Internet access and use the Internet to search for health information, usually in the early stages of care seeking (ie, considering seeking or accepting treatment). [32][33][34][35] In this study, using results from an Internet survey of 10,962 young adults, we developed a multivariate model of intent to not accept a diagnosis of depression, based on the theory of reasoned action as revised by Howland and Hagger 27,28 ( Figure 1). As we measured intention using the Internet in circumstances separate from possible action, we use the term intent to describe our outcome variable.…”
Section: Not Accepting Depression Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Seventy-fi ve percent to 80% of adolescents and young adults have Internet access and use the Internet to search for health information, usually in the early stages of care seeking (ie, considering seeking or accepting treatment). [32][33][34][35] In this study, using results from an Internet survey of 10,962 young adults, we developed a multivariate model of intent to not accept a diagnosis of depression, based on the theory of reasoned action as revised by Howland and Hagger 27,28 ( Figure 1). As we measured intention using the Internet in circumstances separate from possible action, we use the term intent to describe our outcome variable.…”
Section: Not Accepting Depression Diagnosismentioning
confidence: 99%
“…[32][33][34][35] In this study, using results from an Internet survey of 10,962 young adults, we developed a multivariate model of intent to not accept a diagnosis of depression, based on the theory of reasoned action as revised by Howland and Hagger 27,28 ( Figure 1). As we measured intention using the Internet in circumstances separate from possible action, we use the term intent to describe our outcome variable.…”
mentioning
confidence: 99%
“…She attributed the low level of Internet use to low level of connectivity and high cost of cybercafé facilities. In addition, Hanauer, Dibble, Fortin, and Col (2004) surveyed a diverse community college to assess the use of the Internet by the students of health-related information. The survey showed that 83% of Internet users had access to the Internet at their home and 51% of the respondents accessed the Internet at the college or library.…”
Section: Literature Reviewmentioning
confidence: 99%
“…41 With regard to tailoring and adaptation of new technologies, we found that the Internet is a widely accepted source of health information for adolescents and emerging adults; 75% to 80% of this group have Internet access and use the Internet to search for health information. [33][34][35][36] We emphasized control by the emerging adult and local evaluation through the use of a community motivational encounter that emphasizes the emerging adult's role in choosing healthy behaviors, and also by using goal-setting and choice-making throughout the Internetbased intervention. The integration of the intervention into the primary care environment allowed for local evaluation.…”
Section: Formative Research and Intervention Developmentmentioning
confidence: 99%
“…16 Because more than half of all adolescents already use the Internet to seek health information, the Internet is ideally suited for delivery of a behavior change intervention for youth. [33][34][35][36] While there are strong theoretical and empirical rationales for a selfdirected combined primary care Internet-based intervention, there is currently no such intervention available for emerging adults.…”
mentioning
confidence: 99%